Stabilization of compacted clay with cement and/or lime containing peat ash - Mousavi S.E. (Taylor and Francis Ltd., 2023)
Cements; Compression testing; Compressive strength; Embankments; Highway engineering; Lime; Peat; Pozzolan; Scanning electron microscopy; Silica; Silica sand; Soil cement; Soils; Stabilization; Transportation; Chemical compositions; Highway embankments; Partial replacement; Pozzolanic materials; strength; Strength development; Unconfined compression tests; Unconfined compressive strength; Strength of materials